Las bacterias como sistema de expresión de proteínas heterólogas terapéuticas : una revisión bibliográfica (2013)
ABSTRACT: At present, the production of therapeutic proteins has become one of the greatest impact areas at scientific and biotechnological level. The expression of recombinant proteins in prokaryotic systems, particularly in E. coli, has allowed the development of a variety of therapeutic proteins. However, in order to produce functional proteins, a search for balance between quality and production has been necessary. Innovation in strategies to overcome the inherent difficulties to prokaryotic expression systems is essential; thus, it is also crucial delimiting the scope that can have the bacteria most frequently used and those that may represent promising alternatives for the production of proteins of interest. This review aims at conducting a study of state of the art on and the techniques around the use of heterologous protein expression systems on bacteria, with impact on the pharmaceutical and biotechnological industry.